Modeling of Washing Effectiveness in a High-Pressure Washing Device Obtained for Crushed-Stone and Gravel Aggregates - Daniel Saramak; Jarosław Łagowski; Tomasz Gawenda; Agnieszka Saramak; Agata Stempkowska; Dariusz Foszcz; Tomasz Lubieniecki; Katarzyna Leśniak (Resources, 2020)
This article concerns research on washing effectiveness of a high-pressure washing device. Three types of investigations were carried out: Laboratory tests on washing of crushed-stone and gravel aggregate, as well as pilot-scale tests on crushed-stone aggregate. Laboratory tests were conducted for four changeable parameters and pilot-scale investigations for three parameters. All tests were performed based on factorial experiment procedure. For each type of material there was built a model based on multiple regression method. Results of investigations showed that operating pressure in the washer has the highest effect on obtained washing effectiveness, measured as a degree of dust impurities’ removal from feed. The second parameter with the highest impact on washing process effectiveness was the maximum particle of feed, and its relationship to the obtained washing effectiveness appeared inversely proportional. For the crushed-stone aggregate the susceptibility of washing also appeared significant in models.